Effects of Covid-19 Pandemic on Performance of Micro and Small Enterprises (MSEs): A Case of Agri-Businesses in Machakos County, Kenya - Nganu, Margaret; Kalei, Anne; Kilonzo, Thomas (Journal of Business and Management Studies, 2024)
The main objective of the study was to establish the effects of the COVID-19 pandemic on the performance of agribusiness MSEs in Machakos County, Kenya. The study utilized a descriptive research design. The unit of analysis was the agribusiness MSEs involved in mango, avocados, citrus, and dairy value chains. Purposive sampling and simple random sampling were employed, and 198 suitable responses were received. The study identified high operational costs, market inaccessibility, price fluctuations, inadequate cash reserves, and increased competition as the major business risks associated with the COVID-19 pandemic. The study showed that the effects of the COVID-19 pandemic on the performance of agribusiness MSEs in Machakos County were not uniform but value chain dependent, with avocados, mangoes, and citrus being the most affected and the dairy sector experiencing the least effects of COVID-19 pandemic. The major effects of the COVID-19 pandemic included reduced revenues, market inaccessibility, increased spoilage, inaccessible supplies, increased cost of operations, and information gaps leading to shrinkage in profitability. Setting aside cash reserves, using courier services for deliveries, and direct selling were the main coping strategies for the COVID-19 pandemic's effects on businesses. Additionally, adequate stocking and online selling were also used. Moreover, temporary business closure, selling through agents, and value addition were embraced. Pooling of transport with other traders, door-to-door sales, having direct contracts with buyers, selling through cooperatives, and online sales emerged as the main alternative business strategies that have persisted during the pandemic. Reduction in traded volumes, market diversification, collective buying of inputs, and collective marketing have also persisted post-pandemic.
Keywords: Performance, MSES, Agribusiness